Impact of Weight Gain on the Subsequent Survival of New Peritoneal Dialysis Patients - Win Hlaing Than; Jack Kit-Chung Ng; Gordon Chun-Kau Chan; Winston Wing-Shing Fung; Kai-Ming Chow; Cheuk-Chun Szeto (Karger Publishers, 2023)
Introduction: Obesity at the initiation of dialysis was reported to adversely affect the clinical outcome of peritoneal dialysis (PD) patients, and weight gain is common after started on PD. However, there are few studies on the prognostic implications of weight gain after PD. Methods: We reviewed the change in body weight of 954 consecutive patients during the first 2 years of PD in a single Hong Kong center. Their subsequent clinical outcomes, including patient and technique survival rates, hospitalization, and peritonitis rates, were analyzed. Results: The mean age was 60.3 ± 12.2 years; 535 patients (56.1%) were men, and 504 (52.8%) had diabetes. From 1995-1999 to 2015-2019, the percentage of body weight gain during the first 2 years of PD was 1.0 ± 7.9%, 1.6 ± 7.1%, 1.6 ± 7.2%, 3.9 ± 9.5%, to 4.0 ± 10.3% for each 5-year period, respectively (p for linearity 5%, weight loss 2-5%, weight change with 2%, weight gain 2-5%, and weight gain >5% during the first 2 years on PD, respectively (log-rank test, p = 0.035). With multi-variable Cox regression model to adjust for clinical confounders, weight loss >5% during the first 2 years of PD was associated with a worse patient survival rate subsequently (adjusted hazard ratio 4.118, 95% confidence interval 1.040-16.313, p = 0.044), while weight gain was not associated with the subsequent patient survival. Weight change during the first 2 years of PD does not appear to affect subsequent technique survival, hospitalization, decline in residual renal function, or peritonitis rate. Discussion and Conclusions: Weight gain is common during the first two years of PD, but weight gain does not appear to have any significant impact on the subsequent outcome. In contrast, weight loss >5% was significantly associated a worse patient survival subsequently.